(untitled) (SAINTEKBU, 2018)
Marble is one of the industrial materials of high economic value and very beneficial to people’s lives. Therefore, many explorations are done by mining companies. Exploitation of natural resources on a large scale without regard to the carrying capacity of the environment, can lead to drastic decline in the quality of the ecosystem. This is what happened in the post-mine forest area of â€‹â€‹Oenbit Village, North Central Timor District. This study aims to identify and calculate the abundance of plants and environmental factors that affect the plants in the post-marble area of â€‹â€‹Oenbit village. The method used is quadratic / plot method. The results showed that plant species with significant values â€‹â€‹above 80.00% were Anacardium occidentale L. (125.69%), Tamarindus indica L. (122.17%), Tectona grandis L.f (87.32%), and Schleichera oleosa (Lour .) Oken (82.67%). Abiotic environmental factors measured at the study sites are soil pH, soil moisture, air temperature, air humidity and light intensity. The results of these measurements showed no significant difference.